Corruption and Social Trust: Why the Fish Rots from the Head Down - Rothstein, Bo (Social research, 2013)
With the publication of Robert Putnam's 'modern classic' Making Democracy Work in 1993 and his subsequent book, Bowling Alone, in 2000, the issue of social capital has become a huge research industry. Defined as a combination of interpersonal generalized trust and networks based on reciprocity, social capital is seen as a major asset for individuals as well as groups and societies. Although, as he readily admits, Putnam was not the first to put forward the importance of social capital, it was clearly he who showed how it could be used in important (and very ingeniously designed) empirical research (1993). However, when the social capital and social trust research agenda went comparative, it came as a surprise to many that when this concept was being empirically researched, the Nordic countries came out on top irrespective of what measures were being used. Much can be said about the Nordic countries, but not that they are countries with small and noninterventionist governments. Adapted from the source document.